Pendampingan Pelatihan Digital Marketing Pada UMKM Mbah Bendo Koi Guna Meningkatkan Penjualan Dan Pemasaran - Fajerul Dicky Saputra; Jojok Dwiridotjahtjono (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
The growth of digital technology has transformed the global business landscape, including the context of Micro, Small, and Medium Enterprises (UMKM). UMKM hold significant potential to harness the benefits of digital marketing tools to enhance customer engagement and business growth. As an illustrative sector within the realm of UMKM, Koi fish businesses have exhibited substantial changes in their marketing strategies through the adoption of digital technology. The digital marketing approach is capable of establishing brand awareness by selecting social media platforms, planning messaging, and determining promotional strategies. The utilization of social media platforms such as Instagram and Facebook has become pivotal for product promotion, customer interaction, and the cultivation of online communities. Informative and user-friendly websites have also proven to be effective tools for providing product information and supporting purchase decisions. In Blitar, there exist several Micro, Small, and Medium Enterprises (UMKM) focusing on ornamental fish cultivation. One notable example is Mbah Bendo Koi Farm, located at Jl. Kapuas No.92, Bendo Village, Kepanjenkidul Sub-district. Through observation and interviews with the MSME owner, it is evident that the challenge faced by this MSME is its limited marketing efforts, leading to a restricted market reach. Addressing this issue, members of Group 23 have engaged in creating social media accounts and generating content with the aim of attracting new potential customers and expanding the market reach across the entirety of Indonesia. Integrated, creative, and customer-focused digital marketing strategies hold the potential to support business growth and fortify customer relationships.